Cognitive functioning, life satisfaction, and their relationship with the financial attitudes of older individuals who participate in an active aging program (2020)
Life expectancy has increased in many countries throughout the world over recent years, leading to new challenges related to aging. A large part of the population is over 60 years old, and therefore studies that focus on financial autonomy and active aging are necessary. In this paper, we analyze the relationship between cognitive functioning and life satisfaction in relation to financial attitudes in a sample of 251 elderly adults (71% women) participating in an active aging program (M = 67.5, SD = 4.5). We used the Mini-Mental State Examination, the Satisfaction with Life scale, and a questionnaire about financial attitudes to gather data. Our results show that cognitive functioning and life satisfaction are related to certain financial attitudes. We also observed differences associated with gender, education level, and financial independence. According to our findings, life satisfaction should be taken into account when the financial attitudes of older adults are evaluated. The importance of support groups for the elderly is highlighted as well as of all those recreation and health programs, since they constitute a means of promoting well-being.